Effects of siRNA-Mediated Knockdown of GSK3β on Retinal Ganglion Cell Survival and Neurite/Axon Growth - Ahmed, Zubair (Cells, 2019)
There are contradictory reports on the role of the serine/threonine kinase isoform glycogen synthase kinase-3β (GSK3β) after injury to the central nervous system (CNS). Some report that GSK3 activity promotes axonal growth or myelin disinhibition, whilst others report that GSK3 activity prevents axon regeneration. In this study, we sought to clarify if suppression of GSK3β alone and in combination with the cellular-stress-induced factor RTP801 (also known as REDD1: regulated in development and DNA damage response protein), using translationally relevant siRNAs, promotes retinal ganglion cell (RGC) survival and neurite outgrowth/axon regeneration. Adult mixed retinal cell cultures, prepared from rats at five days after optic nerve crush (ONC) to activate retinal glia, were treated with siRNA to GSK3β (siGSK3β) alone or in combination with siRTP801 and RGC survival and neurite outgrowth were quantified in the presence and absence of Rapamycin or inhibitory Nogo-A peptides. In in vivo experiments, either siGSK3β alone or in combination with siRTP801 were intravitreally injected every eight days after ONC and RGC survival and axon regeneration was assessed at 24 days. Optimal doses of siGSK3β alone promoted significant RGC survival, increasing the number of RGC with neurites without affecting neurite length, an effect that was sensitive to Rapamycin. In addition, knockdown of GSK3β overcame Nogo-A-mediated neurite growth inhibition. Knockdown of GSK3β after ONC in vivo enhanced RGC survival but not axon number or length, without potentiating glial activation. Knockdown of RTP801 increased both RGC survival and axon regeneration, whilst the combined knockdown of GSK3β and RTP801 significantly increased RGC survival, neurite outgrowth, and axon regeneration over and above that observed for siGSK3β or siRTP801 alone. These results suggest that GSK3β suppression promotes RGC survival and axon initiation whilst, when in combination with RTP801, it also enhanced disinhibited axon elongation.